P175 Use of a Virtual Clinic to Improve the Lung Cancer Patient Journey. (12th November 2015) - Nanapragasam, A; Maddock, N; McIver, A; Smyth, C; Walshaw, MJ
Abstract : In 2014 with our primary care colleagues we introduced a 'Straight to CT' system for out-patients with a radiological or clinical suspicion of lung cancer. The CT was done on behalf of primary care, and only patients who had a CT suspicious of lung cancer, were automatically taken by the lung cancer team. Such scans are reviewed by a cancer clinician, who makes a provisional next best test plan, and this empowers a telephone clerking by a highly specialised lung cancer nurse. The assessment and plan are documented, and the GP receives a same day fax. We now report our results for the calendar year. Results: 293 patients with suspicious scans were contacted through our virtual clinic, and of these 241 (82%) were triaged to the most appropriate next test as day cases (69 (29%) bronchoscopy, 50 (21%) EBUS, 69 (29%) PET scan, 26 (11%) CT biopsy, 4 (1%) FNA, 17 (7%) pleural aspiration, 6 (2%) bronchoscopy and pleural aspiration). At these attendances, patients were reviewed by medical staff and the CNS who undertook the telephone assessment, and any relevant other assessments performed. Of the remainder, 38 (13%) were triaged to a clinic for assessment, 2 (6%) were admitted, and 2 (6%) referred back to their GP for best supportive care. Using this service we have been successful in targeting cancer resources onto patients subsequently diagnosed with lung cancer (79%), we have improved our mean time to diagnosis to 19 days, with a histological rate of 89%. Our 62 day breach rate is 6%. The new process also provides a 42% cost saving for primary care. Conclusions: We have shown that the use of a virtual clinic can target and speed up the diagnostic pathway for patients with lung cancer. It also makes more efficient use of scarce NHS resources, by ensuring that patients only attend the hospital for necessary investigations. We recommend the use of this innovative service to other clinicians charged with managing this common and distressing disease.